PAKAR PANGAN : PROGRAM KETAHANAN DAN KEMANDIRIAN PANGAN MASYARAKAT DI DESA TANJUNG RAYA - Nasywa Athifah; Widya Ayu Pratiningsih; Riski Amalia; Nadilla Nur Hafizah; ⁠Liona Ayu Permata Kusuma; Ratu Ayunda Giska Renada; Shakila Shakia Raiqa Adinda; Ghazia Rararibatha Annuha; ⁠Gemala Padia; Qurotul Af'idah; Rayhan Juliandra; Natasya Dita Anggraini; Istikomah (PARIPALAKA SRIWIJAYA, 2025)
Food security remains a persistent challenge in many rural areas, including Tanjung Raya Village, Muara Enim Regency, where 70% of household heads were identified as experiencing food insecurity due to limited food reserves and poor access to nutritious food. This community service program aimed to enhance household food security and independence through educational and demonstrative approaches. The two-day program included outreach and hands-on training on composting household organic waste, utilizing home yards with polybag planting, proper food storage, and prevention of cross-contamination. Evaluation showed an increase in participants’ knowledge, with post-test scores rising from 85.80 to 92.25. This program successfully improved community food literacy and encouraged the sustainable use of local resources to strengthen household food security. Keywords: food security, home gardening, compost, food storage